The Ideological Struggle of «Yash Turkistan»: аn Alternative Perspective Against Soviet Propaganda (Based on Issues No. 1-13) - Saidіrakhman U.; Akseit, G. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2025)
The function of Yash Turkistan in thwarting Soviet propaganda is examined in this essay. Throughout the 1920s and 1930s, Turkic intellectuals living abroad battled to preserve national consciousness and the aspiration for independence, while the Soviet government used propaganda to silence critics. By developing a counterargument that revealed the harshness of Moscow’s rule, they opposed Soviet ideological control.This study analyzes Yash Turkistan’s journalistic strategies in opposing Soviet ideology, focusing on its first 13 issues (1929–1930). Using historical-comparative, discourse, and content analysis, it explores how the journal framed Soviet policies as “Red Imperialism” and provided a platform for political awakening.More than an émigré publication, Yash Turkistan functioned as an intellectual platform shaping an alternative historical narrative. Its informational struggle played a key role in preserving national identity. This study examines the efforts of Turkic intellectuals to maintain political consciousness in exile and provides insights into the émigré press’s role in opposing Soviet ideological domination by analyzing its resistance tactics.